Experimental Study on Overtopping Performance of a Circular Ramp Wave Energy Converter - Jamalabadi, Mohammad Yaghoub Abdollahzadeh; Ahmadi, Eisa (Review of Energy Technologies and Policy Research, 2017)
One of the most important debates on energy is planning for the best carriers in each region and determined based on each country’s energy basket. The importance of preserving fossil resources becomes evident when we made the prediction. Iran’s oil and gas resources will finish up to 136 years to 79 years. Since the clean energy production is a new source in interested field of researchers. Here we study the performance of overtopping with a circular ramp which can be used as a model of wave energy converter.